Climate Disinformation — How widespread is it and Who Believes In It? - Čović, Sara; Puzek, Ivan (2025)
The research report offers an overview of the results obtained from a survey study conducted on a representative sample of adult citizens in Croatia (N = 1000) on the topic of climate disinformation. The research was carried out in March 2024 for the project “Facts about the Climate Crisis – klima.faktograf.hr”. The aim of the research was to determine the prevalence, characteristics and factors affecting the acceptance of climate disinformation among the citizens of Croatia.